Prescribing patterns of ophthalmological products in a private sector patient population in South Africa - Ilse Truter (Journal of Applied Pharmaceutical Science, 2014)
Studies on the prescribing patterns of ophthalmological products are scarce. The primary aim of the study was to determine the prescribing patterns of ophthalmological products in a private sector patient population in South Africa. A retrospective drug utilization study was conducted on a 2011 database containing 2 298 312 records for medicine, procedures and medical devices. All records for ophthalmological products were extracted and analysed. A total of 8 428 patients (52.81% males) received 17 087 ophthalmological products. The average age of patients was 36.83 (SD=21.32) years, with 35.92% of products prescribed to patients between 40 and 59 years of age. Anti-infectives accounted for 25.45% of prescribing frequency and 10.63% of prescribing cost, and anti-infectives combined with corticosteroids for 15.44% of prescribing frequency and 17.78% of cost. Only 4.38% of patients received products for glaucoma, accounting for 12.09% of prescribing frequency and 24.66% of cost. The average age of patients on glaucoma products was 61.64 (SD=16.07) years. Antiviral products had the highest average cost (only one trade name, no generic equivalent was available for this product). A third of products were prescribed on a chronic basis. More studies are needed to determine the treatment of eye conditions in South Africa.
Keywords: Ophthalmology, Eye conditions, Drug utilization, Prescribing patterns.